2009
DOI: 10.1039/b815762f
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent attenuation by a single polar-to-nonpolar point mutation of channelrhodopsin-2

Abstract: Channelrhodopsin-2 (ChR2), one of the algal light-gated cation channel rhodopsins, contains five peculiar glutamic acid residues in the N-terminal region corresponding to the second to third transmembrane helices. Here we made systematic mutations of these polar amino acid residues of ChR2 into nonpolar alanine, and evaluated their photocurrent properties. Amongst them, the photocurrent generated by the E97A mutation, ChR2(E97A), was much smaller than expected from its expression. The ChR2(E97A) photocurrent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 42 publications
(35 reference statements)
5
69
0
1
Order By: Relevance
“…However, these negatively charged residues represent a striking feature of helix 2 in our alignment as well (supplemental Fig. S2), and at least some of those were shown to affect the photocurrent (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…However, these negatively charged residues represent a striking feature of helix 2 in our alignment as well (supplemental Fig. S2), and at least some of those were shown to affect the photocurrent (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…They are known to be involved in H Ï© selectivity and H Ï© release. Substitution of Glu-90 by Gln or Asp or His-134 by Arg or Asn inhibited H Ï© conductance and promoted Na Ï© selectivity (27,32,33), suggesting that both residues are responsible for H Ï© transfer and release into the medium or part of the internal selectivity filter. Ritter et al (34) and Radu and co-workers (35,36) monitoring FTIR differences between the dark state and the intermediate P500 reported that ChR2 has two indicative band patterns around 1700 cm ÏȘ1 , implying the existence of two protonated carboxyl residues at least.…”
Section: Alignment-throughout This Study the Residue Numbering Ofmentioning
confidence: 99%
“…Sugiyama et al (32) substituted the glutamates of helix B individually by alanine and found strong inhibition of photoreceptor currents for Ala-82, Ala-83, Ala-97, and Ala-101 but not for Glu-90. The same finding has been reported by Ruffert et al (27), proposing a model for helix B that is very similar to our alignment A, because they propose Glu-90 to be located in the middle of helix B.…”
Section: Alignment-throughout This Study the Residue Numbering Ofmentioning
confidence: 99%
“…S4. Glu-60 was also included in this analysis, although its predicted location is close to the cytoplasmic surface, because this position corresponds to Glu-82 of Chlamydomonas reinhardtii channelrhodopsin 2 (CrChR2), in which its replacement with Ala strongly inhibited photocurrents (10). All but one tested GtACR1 mutant exhibited biphasic current rise and decay, as did wild type (WT), although the rates and contributions of the phases to the total amplitude quantitatively varied (Fig.…”
Section: Significancementioning
confidence: 99%